Analysis of Circulating Microvesicles Levels and Effects of Associated Factors in Elderly Patients With Obstructive Sleep Apnea - Tan, Jin; Xing, Huifang; Sha, Sha; Li, Jinwen; Miao, Yuyang; Zhang, Qiang (Frontiers in Aging Neuroscience, 2021)
Background: The incidence of obstructive sleep apnea (OSA) in the elderly is high, and the disorder is associated with a variety of chronic diseases. Microvesicles (MVs) are extracellular vesicles secreted by various cells during stimulation or apoptosis that play an important role in the pathogenesis of OSA. However, concentrations of circulating MVs in elderly patients with OSA remain unclear. Methods: Patients aged >60 years old were recruited and underwent polysomnography. Circulating plasma MV concentrations, including annexin V+MVs, endothelial MVs (EMVs), platelet MVs (PMVs), and leukocyte MVs (LMVs) levels, were measured using a flow cytometer with different labeling methods. Potential factors affecting the concentration of circulating MVs in elderly patients with OSA were determined via Spearman's correlation and multiple linear regression analysis. Results: Levels of circulating MVs, including both single- (annexin V+MVs, CD144+EMVs, CD41a+PMVs, and CD45+LMVs) and dual-labeled MVs (annexin V+CD144+EMVs), were elevated in elderly patients with OSA. Circulating MVs were positively correlated with OSA severity (AHI, ODI, and SPO2min). To some extent, obesity affected the MV concentrations in elderly patients with OSA. In addition, age and comorbidities may be associated with MV levels, but the correlations between the MV levels and age or comorbidities were not significant. Conclusion: Concentrations of circulating MVs in elderly patients with OSA are associated with the labeling method used, OSA severity, and obesity. The effects of age and comorbidities on circulating MV levels require further verification using a larger sample size.